Pengaruh Kinerja Keuangan, Kebijakan Dividen, Ukuran Perusahaan dan Kepemilikan Manajerial Terhadap Nilai Perusahaan Setelah Initial Public Offering - Setya Wibawa, Kukuh; Yuni, Sri; Christian, Iwan (Universitas Palangka Raya, 2024)
Company size, and managerial ownership on company value after Initial Public Offering (IPO) among property sector companies listed on the Indonesia Stock Exchange from 2019 to 2022. When a company has capital, it has a significant opportunity for expansion to create value growth for the company. The funding obtained at the IPO or its proceeds is determined based on underwriter arguments to establish the company's value according to the reflected information for profit. The ratios used in this research are Financial Performance, Dividend Policy, Company Size, and Managerial Ownership. The research methodology employed in this study is quantitative research, and data collection techniques consist of collecting, recording, and analyzing secondary data in the form of financial reports from property sector companies published by the Indonesia Stock Exchange through its website from 2019 to 2022. The sample in this research was selected using purposive sampling, resulting in a sample of 11 property companies that meet the sample criteria. The data analysis method used is multiple linear regression analysis, and the testing is conducted both partially and simultaneously. The results of this research indicate that financial performance, dividend policy, company size, and managerial ownership do not significantly influence the company's value after IPO. However, when considered simultaneously, financial performance, dividend policy, company size, and managerial ownership collectively influence the company's value after IPO